A review of the genus Pseudokuzicus Gorochov, 1993 (Orthoptera: Tettigoniidae: Meconematidae) - Shi, Fu-Ming; Mao, Shao-Li; Chang, Yan-Lin (Zootaxa, 2007)
A key to species of Pseudokuzicus Gorochov, 1993 is presented. Generic diagnosis are presented. One subgenus and three species are described as new: Similkuzicus subgen. nov., P. (P.) spinus sp. nov., P. (P.) acinacus sp. nov. and P.(S.) quadridentatus sp.nov.. The type specimens are deposited in Museum of Hebei University, Baoding.